Working with Farmers' Groups, An Extension Experience - Yeboah, A. (University of Ghana, 1997)
The study aimed at researching into the prevailing farmers' groups and examine the capability of the nature of farmers' groups and extension interactions with them to influence the expected improvements in their farming activities. The study was carried out in the West Akim district of the eastern region of Ghana. All the twelve FLS in the field as well as the two extension supervisors in the district were interviewed. Fourteen extension farmers' groups and four non-extension farmers' groups were interviewed from five sub-districts. From each farmers' group interviewed five of its members were randomly selected and interviewed. A total of 84 individual farmers were consequently covered in the study. Four other extension supervisors from the DAES as well as three from other extension organisations involved in the study were also interviewed. They included officers in charge of field operations in the district, regional and national headquarters. Data collection started from 14th November 1995 and ended on 18th January 1996. The result of the study revealed that in the West Akim district the DAES deals with both autonomous and sponsored groups. The autonomous groups were found to be more sustainable than the sponsored groups.'The sustainability of the autonomous groups was attributed to their nature, mode of format and the existing internal dynamics. In sustainable groups the extension agent has the opportunity to plan for series of lessons which together can bring about improvements in the farming activities of group members.„ The nature of a farmers' group thus affects its sustainability and the opportunity for extension agent and farmers to teach and acquire knowledge respectively. The effectiveness of extension delivery is also influenced by the nature of farmers' groups. The extension agents of the DAES'were not able to arrange and meet farmers' groups according to the visit schedules as envisaged under the T-&V system being practised by the DAES. The expected two weeks interval between consercutive meetings of extension agents and farmers' groups was not fully achieved. Thus regular teaching and learning opportunities were not created by the extension agents. The monthly: training sessions which could have reinforced the extension delivery skills of the extension agents were directed towards technical topics. Extension agents were not adequately equipped to contribute much to the social life of farmers' groups. Extension interaction with extension and non-extension farmers' groups in the West Akim district enhanced the production levels of farmers, but not much was achieved in the development and sustainability of the farmers' group life. To work effectively and efficiently with farmers' groups, extension organisations among others need to renew and meet the needs of their clients, and also train their agents to be adept in working with farmers' groups and encouraging farmers to form their groups.
Thesis(MPhil)- University of Ghana, 1997.